The influence of morphological characteristics on the specific motor skills of junior-age karate athletes - Dušica Rakita; Dušan Rakonjac; Mila Vukadinović-Jurišić; Jelena Obradović (University of Novi Sad, Faculty of Sport and Physical Education, 2018)
The aim of this study was to determine the relations between morphological characteristics and specific motor skills of karate athletes, where by the obtained results would be used in better planning and programming of training. Twenty-five young adults karate athletes (15.32 ± 0.22 years) members CC "Šotokan" from Loznica with a sports experience of not less than 8 years participated in this study. The research involved the measurement of certain morphological characteristics and specific motor skills of forward hand punch and foot strikes using standardized tests. The application of the regression analysis showed that there is a statistically significant influence of the system of predictor variables on the criterion variables (p≤0.05) reverse punch - gyaku-zuki (P=0.00), lunge punch - oi-zuki (P=0.00) and front kick - mae-geri (P=0.01). The total variability ranged from 50% of the criterion of the front kick - mae-geri to 60% of the criterion of lunge punch - oi-zuki. The values of the standardized regression coefficient Beta indicate the individual positive and statistically significant influence of the body height and muscle mass variables on the criteria tested: gyaku-zuki, oi-zuki and mae-geri, and the negative impact of the body weight variable on the oi-zuki criterion (pβ≤0,05). A positive influence of the overall body water quantity variable on the gyaku-zuki criterion (pβ≤0,05) was also determined. It can be concluded that there is a connection between the morphological characteristics and the specific motor skills of junior-age karate athletes from Loznica.